O trabalho mediado por TIC - Tecnologias de Informação e Comunicação e seus efeitos sobre o trabalhador - Jaqueline Abreu Vianna (2012)
This thesis presents a reflection on the work activities that can be mediated by Information and Communication Technologies ICT, emphasizing the impacts observed in different dimensions of the workers life. By immersing in the scope of work and its organization, the research relates the connection between ICT, work space and everyday life. It was sought to perceive how time and space relationship transformed by the possibility of flexible workspaces correlates with the various dimensions of the workers life. It is highlighted an important variable that this thesis discusses: the mixture of spaces and their meanings. Home and office, leisure and work as evidence of an ambiguity present in the working modality researched. To understand the ICT mediated work, it was imperative to go through the evolution of the capitalist mode of production, recognizing that its premises are increasingly present today. Hence, the thesis begins the discussion of the theme contextualizing the object of study within the evolution of work processes, according to Marxian array, pointing to the maintenance and, why not say, to the strengthening of the main pillars in the elimination of production barriers related to time and space. The emancipation of space and the independence of time for the production have been explored in this thesis as intrinsic elements to the working modality studied. As implications of the ICT mediated work, or affected dimensions in the workers life, the following variables were analyzed: the work invasion on domestic spaces, the forms of domination and control exercised over the worker, the lack of a ICT mediated work regulation, identity, sociality, health, the use and retrieval of information at work. The home invasion and the using up of privacy by the work proved to be specially prominent and directly correlated to the workers overloading and illness. The intensification of work, flexibility and the speed also emerged as elements that go through both work organization forms and own interpersonal relations.